2020
DOI: 10.1021/acsomega.0c03784
|View full text |Cite
|
Sign up to set email alerts
|

Walnut Consumption Induces Tissue-Specific Omega-6/Omega-3 Decrease in High-Fructose-Fed Wistar Rats

Abstract: Increased dietary, blood, and tissue n-6/n-3 fatty acid ratios are associated with obesity and metabolic syndrome. Due to Westernized dietary patterns, the increasing n-6/n-3 ratio is of growing concern worldwide, and dietary strategies aimed at its lowering are of public health importance. Walnuts are rich in dietary fats, and their consumption promotes cardiometabolic health. This study aimed to examine the effect of 6-week walnut consumption on tissue-specific n-6/n-3 ratio and fatty acid metabolic conversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…In addition, we demonstrated an increased omega-6/omega-3 ratio in FRD rats, which has been suggested to be highly prothrombotic and proinflammatory and to contribute to the prevalence of atherosclerosis and MetS-related diseases [ 16 , 42 ]. The tissue-specific omega-6/omega-3 decrease after walnut consumption in high-fructose-fed Wistar rats was recently demonstrated [ 37 ]. An increase in the AA/EPA ratio as a result of fructose feeding in our study could be deleterious for the heart; previously, it has been suggested that higher levels of the AA/EPA ratio are associated with a greater risk for CVD and has been proposed as a biochemical marker of CVD events [ 16 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we demonstrated an increased omega-6/omega-3 ratio in FRD rats, which has been suggested to be highly prothrombotic and proinflammatory and to contribute to the prevalence of atherosclerosis and MetS-related diseases [ 16 , 42 ]. The tissue-specific omega-6/omega-3 decrease after walnut consumption in high-fructose-fed Wistar rats was recently demonstrated [ 37 ]. An increase in the AA/EPA ratio as a result of fructose feeding in our study could be deleterious for the heart; previously, it has been suggested that higher levels of the AA/EPA ratio are associated with a greater risk for CVD and has been proposed as a biochemical marker of CVD events [ 16 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, these animals displayed normoglycemia, elevated serum insulin and triglyceride levels, and increased adiposity and body weight. 17,18 Walnut kernels were administered at a dose of 2.4 g per day for 6 weeks. Special care was taken to ensure that each animal regularly consumed a provided daily dose of walnut kernels.…”
Section: Animals and Dietsmentioning
confidence: 99%
“…The fatty acid composition in the brain tissue was determined according to the methodology described previously. 18 Briefly, total lipids were extracted following the Folch method, using chloroform-methanol (2:1, v/v) with 0.05% (w/v) butylated hydroxytoluene. 24 Furthermore, fatty acids were esterified to methyl esters with 3 mol L −1 hydrochloric acid in methanol with 2% (w/v) butylated hydroxytoluene, then incubated, mixed with hexane, centrifuged and dried under N 2 stream.…”
Section: Analyses Of Fatty Acids In Brain Total Lipid Poolmentioning
confidence: 99%
See 1 more Smart Citation
“…NAFLD development is also associated with genetic makeup such as the Patatin-like phospholipase domain-containing 3 (PNPLA3) polymorphism [93]; therefore, investigating the interactions between walnut and genes would be helpful to understand the individually different effects of walnut on NAFLD. Male C57BL/6J mice Walnut oil capsule (6, 12, 18 mL/kg) through intragastric administration with D-galactose injection Improved hepatic necrosis, hydropic degeneration, vacuolar degeneration, and lymphocytic infiltration along with increased total anti-oxidant capacity [97] Male Wistar rats Walnut-enriched diet (2.4 g/day) with high fructose in drinking water (10% w/v) Lowered the n-6/n-3 ratio in plasma, liver and epididymal adipose tissue, and increased LA and αLNA contents in the liver [98] Participants with obesity (n = 10) Randomized placebo-controlled crossover clinical trial with five-day consumption of either walnuts (48 g/day) or placebo Improved the lipid profile and reduced insulin resistance and blood levels of ceramides, sphingomyelins, and N-glycans [74] Participants with abdominal obesity and dyslipidemia (n = 278)…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%